Highly stretchable, compliant, polymeric microelectrode arrays for in vivo electrophysiological interfacing - Qi, Dianpeng (2020)
Polymeric microelectrode arrays (MEAs) are emerging as a new generation of biointegrated microelectrodes to transduce original electrochemical signals in living tissues to external electrical circuits, and vice versa. So far, the challenge of stretchable polymeric MEAs lies in the competition between high stretchability and good electrode-substrate adhesion. The larger the stretchability, the easier the delamination of electrodes from the substrate due to the mismatch in their Young's modulus. In this work, polypyrrole (PPy) electrode materials are designed, with PPy nanowires integrated on the high conductive PPy electrode arrays. By utilizing this electrode material, for the first time, stretchable polymeric MEAs are fabricated with both high stretchability (≈100%) and good electrode-substrate adhesion (1.9 MPa). In addition, low Young's modulus (450 kPa), excellent recycling stability (10 000 cycles of stretch), and high conductivity of the MEAs are also achieved. As a proof of concept, the as-prepared polymeric MEAs are successfully used for conformally recording the electrocorticograph signals from rats in normal and epileptic states, respectively. Further, these polymeric MEAs are also successful in stimulating the ischiadic nerve of the rat. This strategy provides a new perspective to the highly stretchable and mechanically stable polymeric MEAs, which are vital for compliant neural electrodes.